Association between high-risk HPV types, HLA DRB1* and DQB1* alleles and cervical cancer in British women - Cuzick, J (Nature Publishing Group, 2000)
Cervical scrapes from 116 British women referred with cervical cancer were tested for the presence of high oncogenic risk human papillomavirus (HPV) genotypes (HPV(hr)). Ninety-four per cent of the scrapes had one or more of these virus types and 66% were HPV16-positive. HPV18 was more frequent in adenocarcinoma. No evidence was found for an increased cancer risk associated with the HPV16 E6 350G variant. The HLA DRB1* and DQB1* alleles in these women and in 155 women with normal cytology and negative for HPV(hr)DNA were compared. DQB1*0301 alone (2P = 0.02) and in combination with DRB1*0401 (2P = 0.02) was found to be associated with cervical cancer. This was more marked in cancers positive for HPV types other than HPV16. In contrast, DRB1*1501 alone and in combination with DQB1*0602 was not significantly elevated in cancers overall, but did show some excess in HPV16-positive cancers (2P = 0.05), associated with HPV16-positive cervical cancers. Taking all cancers together, a marginally significant protective effect was found for DQB1*0501 (2P = 0.03) but no protective effect could be seen for DRB1*1301. © 2000 Cancer Research Campaign